Fifth annual report - Mew, E. B. ; Miller, Mary F. ; Norman, E. M. ; Roberts, D. ; Galbraith, H. ; Worden, M. ; Daukes, A. ; Waterworth, E. M. ; Mottram, D. B.; Capener, Norman (1932)
1932 1932 1930s 86 pages : illustrations Your Daily Bread. BUY HILL'S AND HAVE The Best. C. J. S. HILL & SON. 19, 20 & 21 CUFTON ROAD, 'Phone 3125. EXETER 'Phone 3125. made like a surgical knife THE "SERVICE" blades are made by men skilled in the manufacture of surgical knives, and their cutting edges specially hardened and finished to lengthen the life of the blade. One trial will convince you that here is the super blade for which you have longed. Send 1/6 for a trial packet to-day. "SERVIC" BLADE 12 for 1/6 SURGICAL MANUFACTURING CO., 85 MORTIMER STREET, LONDON, W.1. [Picture] EACH PACKET CONTAINS 12 BLADES. EACH BLADE FINISHED BY HAND. BY MEN SKILLED IN THE MAKING OF SURGICAL KNIVES. 74 292/841.51/2/2